The Effect of Glioblastoma Tumour Microenvironment on the Modulation of the Immune System - Mora Ruiz, Guillermo; Bayona Rollo, Clara; Ochoa Garrido, Ignacio (Jornada de Jóvenes Investigadores del I3A, 2024)
Glioblastoma (GBM) is the most common and lethal malignant primary brain tumour in adults. Understanding its function and microenvironment is crucial to develop effective treatments. In this study, we optimized the co-culture of glioblastoma cells with immune cells by measuring cytokine secretion with interleukin-2 stimulation in different environments.